Teacher Preparedness and Resource Allocation in Inclusive Classrooms: Evaluating Secondary Schools in Aligarh District - Sana Fatimah; Arif Mansoor Khan (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This study aims to evaluate the level of teacher preparedness and the effectiveness of resource allocation in the implementation of inclusive education in secondary schools in Aligarh District, Uttar Pradesh, India, during the 2023–2025 period. Using a descriptive-evaluative quantitative approach with a sample of 150 teachers, data were collected through structured questionnaires and school resource audits. The results indicate that teacher preparedness falls into the moderate category, where positive attitudes toward inclusion are not yet matched by adequate technical competencies in curriculum modification. Resource allocation was found to be at a critical level, particularly in terms of assistive technology and the availability of special education experts. The analysis shows a significant positive correlation between resource adequacy and teacher self-efficacy. This study concludes that systemic failures in providing infrastructure and managerial support are the main obstacles to the success of the National Education Policy (NEP) 2020 at the local level. It is recommended to restructure the education budget for digital technology and adopt teacher training models based on practical mentoring.